Pengaruh Pembiayaan Ijarah Dan Biaya Operasional Pendapatan Terhadap Profitabilitas Bank Syariah Mandiri - Sabik Khumaini; Nurul Fathiya Armina (Prodi Perbankan Syariah FAI UMT, 2019)
This study was conducted to examine the effect of Ijarah financing variables and Operational Income Operational Costs (BOPO) on the profitability of ROA (Return on Assets) at Bank Syariah Mandiri. The analysis technique used is multiple regression analysis and hypothesis testing using partial t test, F test simultaneously with a significance level of 5% and the coefficient of determination test. In addition, classical tests are also carried out which include the normality test, the heteroscedasticity test, the autocorrelation test and the multicollinearity test. The conclusions obtained are based on the results of the calculated hypothesis testing, showing the variable Ijarah and BOPO significantly negative effect on Return on Assets (ROA) in the period 2006-2015. Meanwhile, the results of the statistical F test, the independent variables Ijarah and BOPO together have a significant effect on the dependent variable ROA with a probability value of less than 0.05. The predictive ability of the two variables on ROA is 24.7%. While the remaining 75.3% was accepted by other factors outside the regression model. Kata kunci: Pembiayaan, Ijarah, Pendapatan, Profitabilitas